The Impact of Endorsements on Sales Turnover Msme Business in Bandar Lampung City - Anggun Yustia Arinda T; I Wayan Suparta; Arivina Ratih YT (International Journal Labs, 2022)
Background: Technological developments are currently widely used by business actors to promote their products, with the convenience desired by buyers, of course, this is a solution for MSME entrepreneurs for business development. The use of endorsements is one alternative that can be tried to increase sales turnover. Objective: This study aims to determine the extent of the role of teachers in implementing inclusive education services at SMAN 6 Bandung. Method: This research was conducted using a survey using the help of a google form on 100 respondents of MSME entrepreneurs who used endorsements as assistance for promoting MSME businesses in Bandar Lampung City. This type of research uses a quantitative type of research using a descriptive format. The data collected in the analysis used quantitative descriptive and qualitative descriptive methods by utilizing descriptive statistical tools and tables of single frequencies and cross frequencies. Decision-making is seen from the number of percentage results if more than 50% is interpreted as a variable that has an impact on MSMEs. Results: The results of this study obtained the use of promotion using social media with the help of endorsers to promote products owned by MSMEs greatly affect the information aspect, persuasive aspect, repetition aspect, and sales turnover to develop and compete with other MSMEs. Conclusion: This study focuses on the impact of the effect of endorsements on MSME turnover, especially on sales volume and profit. The use of promotion using social media with the help of endorsers to promote products owned by MSMEs has a great impact on information aspects, persuasive aspects, repetition aspects, and sales turnover to develop and compete with other MSMEs.